Distinctness Between Taxonomic and Functional Diversity Indexes of Bryozoan-Associated Decapods in Southeastern Brazil - Rodrigues, G. F.B. [UNESP]; Zacari, L. [UNESP]; Trevisan, M. R.R. [UNESP]; Moraes, I. R.R.; Castilho, A. L. [UNESP] (Springer Nature, 2025)
Microhabitat complexity is a key factor in enhancing species diversity across ecosystems. Sessile invertebrates contribute to this complexity by forming biogenic structures, promoting species diversity and coexistence through resource partitioning and refuges provisioning. This study investigates the community structure of three decapod infraorders (Anomura, Brachyura, and Caridea) associated with bryozoan colonies on artificial pilings in Ubatuba Bay, Brazil. We hypothesized that diversity would differ among infraorders when using traditional taxonomic indices but would show similar patterns when functional diversity indices were applied. Fieldwork conducted from September 2019 to May 2023 involved sampling decapods from Schizoporella sp. colonies at a depth of 4 m. We identified 28 species across the infraorders, with significant differences observed in taxonomic diversity but not in functional diversity. Brachyura exhibited higher species richness and taxonomic diversity compared to Anomura and Caridea. However, functional diversity indices did not differ significantly among the infraorders, suggesting that Schizoporella sp. colonies may act as a biotic filter, selecting species with traits conducive to survival in these microhabitats. Our findings highlight the importance of integrating taxonomic and functional diversity indices in ecological studies, particularly in environments where specific traits influence community assembly. The results contribute to understanding the role of biogenic structures in shaping marine biodiversity and offer insights into biodiversity conservation in rocky subtidal zones.
Keywords: Biogenic structures; Diversity patterns; Functional dispersion; Functional evenness; Functional richness